SuhB is an integral part of the ribosomal antitermination complex and interacts with NusA. Issue 12 (25th May 2019) - Dudenhoeffer, Benjamin R; Schneider, Hans; Schweimer, Kristian; Knauer, Stefan H
Abstract: The synthesis of ribosomal RNA (rRNA) is a tightly regulated central process in all cells. In bacteria efficient expression of all seven rRNA operons relies on the suppression of termination signals (antitermination) and the proper maturation of the synthesized rRNA. These processes depend on N-utilization substance (Nus) factors A, B, E and G, as well as ribosomal protein S4 and inositol monophosphatase SuhB, but their structural basis is only poorly understood. Combining nuclear magnetic resonance spectroscopy and biochemical approaches we show that Escherichia coli SuhB can be integrated into a Nus factor-, and optionally S4-, containing antitermination complex halted at a ribosomal antitermination signal. We further demonstrate that SuhB specifically binds to the acidic repeat 2 (AR2) domain of the multi-domain protein NusA, an interaction that may be involved in antitermination or posttranscriptional processes. Moreover, we show that SuhB interacts with RNA and weakly associates with RNA polymerase (RNAP). We finally present evidence that SuhB, the C-terminal domain of the RNAP α-subunit, and the N-terminal domain of NusG share binding sites on NusA-AR2 and that all three can release autoinhibition of NusA, indicating that NusA-AR2 serves as versatile recruitment platform for various factors in transcription regulation.